Pediatric Stroke Impairs Theory of Mind Performance. (March 2020) - Lo, Warren; Li, Xiangrui; Hoskinson, Kristen; McNally, Kelly; Chung, Melissa; Lee, JoEllen; Wang, Ji; Lu, Zhong-Lin; Yeates, Keith
Aim: This pilot study explored whether childhood stroke impairs performance on theory of mind (ToM) tasks and whether ToM task performance correlates with resting state connectivity in brain regions linked with social cognition. Method: We performed a case-control study of 10 children with stroke and 10 age- and gender-matched controls. They completed 2 ToM tasks, and resting state connectivity was measured with functional magnetic resonance imaging (MRI). Results: Children with stroke performed worse than controls on conative ToM tasks. Resting state connectivity in the central executive network was significantly higher and connectivity between right and left inferior parietal lobules was significantly decreased in children with stroke. Resting state activity and ToM performance were not significantly correlated. Interpretation: Childhood stroke results in poorer performance on specific ToM tasks. Stroke is associated with changes in resting state connectivity in networks linked with social cognition including ToM. Although the basis for these changes in connectivity is not well understood, these results may provide preliminary insights into potential mechanisms affecting social cognition after stroke. The findings suggest that further study of the effect of childhood stroke on network connectivity may yield insights as to how stroke affects cognitive functions in children.